Immune Checkpoint Inhibitor-Induced Hypophysitis and Patterns of Loss of Pituitary Function - Jessel, Shlomit; Weiss, Sarah A.; Austin, Matthew; Mahajan, Amit; Etts, Katrina; Zhang, Lin; Aizenbud, Lilach; Perdigoto, Ana Luisa; Hurwitz, Michael; Sznol, Mario; Herold, Kevan C.; Kluger, Harriet M. (Frontiers in Oncology, 2022)
Background: Immune checkpoint inhibitors (ICI) are clinically active across multiple tumor types but the associated immune-related adverse events (irAEs) lead to treatment delays or discontinuation and negatively impact quality-of-life. Hypophysitis is often a permanent irAE that may affect multiple pituitary hormonal axes. Here we comprehensively characterize our institution’s clinical experience with ICI-induced hypophysitis and the associated patterns of pituitary function loss. Methods: Patients with solid tumors, mostly melanoma and renal cell carcinoma (RCC), treated with ICI at Yale Cancer Center were prospectively enrolled from October 2016-May 2021. Demographics and clinical data were obtained from the medical record including type and timing of irAEs. Patients were included in this cohort if hypophysitis was diagnosed by pre-specified biochemical and clinical parameters. Results: The overall incidence of hypophysitis was 69/490 (14%) in patients with melanoma (n=58, 84%), RCC (n=10,14%), and merkel cell carcinoma (n=1, 1%) who received ipilimumab plus nivolumab (77%; 53/69), anti-PD-(L)1 (17%; 12/69), or ipilimumab monotherapy (6%; 4/69). Median time to hypophysitis on combination ICI versus anti-PD-1 was 2.8 vs. 4.1 months. The incidence of hypophysitis in patients with melanoma was 25% (46/187) with ipilimumab plus nivolumab and 5% (7/129) with anti-PD-(L)1 compared to 9% (7/77) and 8% (3/37), respectively, in patients with RCC. Patients who developed hypophysitis on combination ICI had a higher rate of headache (p=0.05) and co-occurring irAEs (p=0.01) compared anti-PD-(L1)1 monotherapy. At a median follow-up of 2.2 years, 77% of patients were alive. Objective response rates to ICI in melanoma patients were higher than previously reported for unselected populations. Central hypothyroidism and hypogonadism were the most common pituitary axes affected after the adrenal axis. In select cases, there was evidence of spontaneous rebound in free testosterone levels after an initial decline. Conclusions: We demonstrate a higher rate of ICI-induced hypophysitis than previously reported, which may be reflective of real-world practice due to increased awareness as experience with ICI has grown. In select cases, there was evidence of rebound in free testosterone and/or gonadotropins but not in adrenal axis hormones.